Hubungan antara inkontinensia dengan depresi pada lanjut usia di Panti Wreda Dharma Bakti Pajang Surakarta - Chesor, Mis Aneesah; , Supratman, SKM , M.Kes., Ph.D; , Kartinah , S.Kep (2015)
Urinary incontinence is a common problem of the older people. Inkontenence in the elderly may result in a decrease in the quality of life of the elderly which is the personal appearance (body image) elderly. Conditions of quality of life and low self-esteem causing concern to the elderly living conditions and ultimately can bring on the condition of elderly depression. This study aims was to determine investigate the relationship between urinary incontinence and depression at Panti Wredha Dharma Bakti Pajang Surakarta. The research design was a cross sectional. The target population was the elderly aged 60-95 years who experience urinary incontinence at the Panti Wredha Dharma Bakti Pajang Surakarta. Sample siz of study were 43 elderly take by simple random sampling. Collecting data used questionnaires Sandvix Severity Index (SSI) and Geriatric Depression Scale (GDS). Data were analyzed using Chi Square test. The study concluded that (1) the level of urinary incontinence in the elderly is largely moderate incontinence, (2) the level of the majority of elderly depression is no depressive symptoms (normal), and (3) there is a relationship between urinary incontinence and depression in the elderly in Panti Wredha Dharma Bhakti Pajang Surakarta and urinary incontinence is a risk factor for the onset of depression in the elderly.